Biochemical composition of Meretrix meretrix in the Bakkhali river Estuary, Cox's Bazar, Bangladesh - Joydeb Chowdhury; Mohammad Saydul Islam Sarkar; Md. Ashraful Azam Khan; Md. Simul Bhuyan (Annals of Marine Science - Peertechz Publications, 2019)
The present study was conducted in the Bakkhali river estuary, Cox's Bazar, Bangladesh from September 2012 to July 2013. Percentage of protein was the main component of the biochemical composition in the mussels followed by carbohydrate, ash, and lipid. The proximate composition of Meretrix Meretrix revealed that it contained protein (12.184-14.291%), lipid (0.721-0.922%), ash (2.435- 3.201%), moisture (77.0-78.9%) and carbohydrate (4.914-5.907%). The mineral content of the Meretrix Meretrix were Ca (0.601-0.801 mg/g), Fe (0.070-0.099 mg/g) and phosphorus (0.300-0.794 mg/g).